Perlindungan Hukum Terhadap Konsumen dalam Transaksi Jual Beli Online di Era Digitalisasi Ekonomi - Naila Nirmala; Desi Rosita; Putri Fatima (Legal Note, 2025)
The rapid development of information technology has transformed trading patterns from conventional systems into digital platforms through e-commerce. This phenomenon provides convenience for society in conducting buying and selling activities, yet it also raises various legal issues related to consumer protection. This study aims to analyze the forms of legal protection for consumers in online transactions in Indonesia and to identify the obstacles in its implementation. The research method used is a normative juridical approach by examining relevant regulations such as Law No. 8 of 1999 on Consumer Protection and Law No. 11 of 2008 on Electronic Information and Transactions (ITE Law). The results of the study show that, normatively, consumer protection is clearly regulated through existing legislation; however, its implementation still faces several obstacles, such as weak supervision of online business actors, low consumer legal awareness, and limited enforcement mechanisms. Efforts to enhance consumer protection can be carried out through strengthening supervisory institutions, increasing consumer education, and improving collaboration among the government, business actors, and the community to create a safe and fair digital ecosystem. Therefore, the presence of law is expected to serve as a regulatory instrument that adapts to technological developments while ensuring safety and justice for consumers in the increasingly complex era of economic digitalization.